1990
DOI: 10.3354/meps062161
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of degrading Spartina alterniflora lignocellulose to the dissolved organic carbon pool of a salt marsh

Abstract: As Spartina alter~~iflora lignocellulose degrades, it contributes soluble degradation products to the bulk dssolved organic carbon (DOC) pool in salt marsh environments. Experiments with radlolabeled S. alterniflora hgnocelluloses show that during the initial 6 mo of decomposition, DOC accounts for 50 to 60% of the total degradation products (DOC plus CO2) of the lignin fraction of hgnocellulose; by contrast, only 20 to 30 '10 of the polysaccharide portion of S alterniflora lignocellulose accumulates as DOC du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 9 publications
(10 reference statements)
3
33
0
Order By: Relevance
“…Valiela et al (1984) observed that weight losses from Spartina during the initial stages of decomposition -were similar under both aerobic and anaerobic decomposition. It appears that all of the major components of Spartina, including polysaccharides and lignin, are susceptible to leaching during the first month of decomposition (Benner et al 19863;Moran and Hodson 1990). A portion of these relatively insoluble polymers is also readily leached from various other vascular plant tissues (Benner et al 19863, 1990b).…”
Section: Resultsmentioning
confidence: 99%
“…Valiela et al (1984) observed that weight losses from Spartina during the initial stages of decomposition -were similar under both aerobic and anaerobic decomposition. It appears that all of the major components of Spartina, including polysaccharides and lignin, are susceptible to leaching during the first month of decomposition (Benner et al 19863;Moran and Hodson 1990). A portion of these relatively insoluble polymers is also readily leached from various other vascular plant tissues (Benner et al 19863, 1990b).…”
Section: Resultsmentioning
confidence: 99%
“…depositional environments (Gardner & Menzel 1974, Hedges & Parker 1976, Wilson et al 1985, Requejo et al 1986, Haddad & Martens 1987, Hamilton & Hedges 1988 and to pools of dissolved organic carbon in both freshwater and marine environments , Meyers-Schulte & Hedges 1986, Moran & Hodson 1990. In addition to providing a biomarker which is unique to vascular plants, the CuO oxidation products of lignin contain more detailed information characteristic of the plant tissue source Vanillyl phen o l~ a r e predominant reaction products of woody and herbaceous tissue.…”
Section: Days In Fieldmentioning
confidence: 99%
“…Leaching of DOC from plant tissues can occur both during tidal submergence and aerial exposure (Gallagher et al 1976, Turner 1978, Pakulski 1986, Moran & Hodson 1990, Turner 1993, Mann & Wetzel 1996. Table 3.…”
Section: Macrophyte Carbon Budgetmentioning
confidence: 99%